If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 100 = 10x * 10 Reorder the terms for easier multiplication: 100 = 10 * 10x Multiply 10 * 10 100 = 100x Solving 100 = 100x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-100x' to each side of the equation. 100 + -100x = 100x + -100x Combine like terms: 100x + -100x = 0 100 + -100x = 0 Add '-100' to each side of the equation. 100 + -100 + -100x = 0 + -100 Combine like terms: 100 + -100 = 0 0 + -100x = 0 + -100 -100x = 0 + -100 Combine like terms: 0 + -100 = -100 -100x = -100 Divide each side by '-100'. x = 1 Simplifying x = 1
| 3n^2+6n-73=0 | | 0.5x=-65 | | -80.2+n=-85 | | 12x^2-6x+15= | | (-6.3x+5)(-4)= | | d*0.3=9 | | X^2+3/5-1=0 | | 9p+.75d=75 | | 12z^2+5z-3=0 | | 25x-276=x-108 | | (15/x)+(9x-7/x+2)=9 | | 8(w)-6.4=6.4+5(w) | | 10z^2+3z-1=0 | | 3x-15=3y+37 | | (5x-2)/(x-4)=-3 | | 8w-6.4=6.4+5w | | 7x^2=14x-13/9 | | -2y-6/3=x | | (3/2x)-(5/3x)=2 | | 3x+2x+6=15 | | 2x+134=5x+182 | | (x)+2(x+1)=119 | | 9z-34=4z-6 | | 3x^2+24x+3y^2=0 | | x(8-x)+1whenx=-6 | | (2w-2)(w)=112 | | 5m-15m=70 | | 5(x+8)-4whenx=4 | | 6(5a-b)-6(7b-7a)= | | -1/99y=0 | | a/2.4=26 | | -2/5y=-14 |